Physical Fitness Profile of Eighth Grade Students at SMP Negeri 7 Pangaribuan, North Tapanuli Regency - Siregar, Jeremia Kevin; Lubis, Ade Evriansyah (Educational Sciences Journal, 2025)
This study aimed to identify the physical fitness profile of eighth-grade students at SMP Negeri 7 Pangaribuan, North Tapanuli Regency, during the 2023/2024 academic year. The research employed a quantitative descriptive method using a series of physical fitness tests developed by the Indonesian Physical Fitness Workshop (1984), which included five components: a 50-meter sprint, pull-ups, sit-ups, vertical jump, and a 1000-meter run. The participants consisted of 34 students (20 male and 14 female) selected through purposive sampling. Data were analyzed using normative scoring and percentage classification. The findings revealed that the students’ overall level of physical fitness was categorized as “Moderate,” with an average total score of 16.74. Specifically, 68% of students were in the moderate category, 29% in the good category, and 3% in the poor category. These results indicate that the students’ physical fitness levels require further improvement through consistent and structured physical education programs.